2015
DOI: 10.2214/ajr.14.13375
|View full text |Cite
|
Sign up to set email alerts
|

Renal Masses With Equivocal Enhancement at CT: Characterization With Contrast-Enhanced Ultrasound

Abstract: Contrast-enhanced ultrasound is effective for characterizing renal lesions presenting with equivocal enhancement at CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…While MRI has its own advantages such as no ionizing radiation, better contrast resolution and functional information, it is more susceptible to artifacts, and most community-acquired MR scans have less image resolution [14] . It is also reported that CEUS is effective for characterizing renal tumors presenting with equivocal enhancement at CT [15] . CEUS is well suited to help in the evaluation of the enhancement curve over time, which aids in preoperative differentiation of renal tumors [16] .…”
Section: Discussionmentioning
confidence: 98%
“…While MRI has its own advantages such as no ionizing radiation, better contrast resolution and functional information, it is more susceptible to artifacts, and most community-acquired MR scans have less image resolution [14] . It is also reported that CEUS is effective for characterizing renal tumors presenting with equivocal enhancement at CT [15] . CEUS is well suited to help in the evaluation of the enhancement curve over time, which aids in preoperative differentiation of renal tumors [16] .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the ability of CEUS to identify renal infarction and to characterize complex cystic masses, pseudolesions, and hypovascular lesions has been mostly demonstrated in patients with well-functioning kidneys[10,12,13,21]. To our knowledge, no specific studies focused on patients with renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning CEUS, we used the following diagnostic criteria: (1) infarction was diagnosed in presence of at least one well-defined, wedge-shaped non-enhancing area within an otherwise normal-appearing kidney[12]; (2) cortical ischemia was diagnosed in presence of enhancing interlobar and arcuate arteries with non-enhancing portions of the cortex[11]; and (3) a lesion was considered solid if more than half of the volume was represented by enhancing solid tissue, and cystic if composed predominantly of nonenhancing spaces[10,20]. Cystic lesions were graded according to the Bosniak criteria as previously described[13,14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations